One health approach to Balantioides coli: Molecular and metabarcoding evidence of zoonotic transmission - Camila Souza Carvalho Class; Pedro Mendes de Souza; Renan de Souza Ferreira; Ingrid da Silva Reis; Laís Lisboa Corrêa; Breno Torres da Silva; Gabriella Ribeiro Vaz da Costa; Fabiana Batalha Knackfuss; Roberto Júnio Pedroso Dias; Alynne da Silva Barbosa (PLoS ONE, 2026)
Balantioides coli is a neglected zoonotic protozoan, with pigs recognized as its main reservoirs. In tropical countries such as Brazil, information on balantidiasis in occupationally exposed human populations remains limited. In this context, this study investigated the occurrence of B. coli and other intestinal parasites in pig farmers, their families, and pigs from the same farms, while also exploring associations with sanitary conditions and the gut microbiota. Fecal samples from 47 humans and 15 pigs from family-owned and industrial farms in Rio de Janeiro and Minas Gerais, Brazil, were analyzed. General and sanitary information was obtained through structured questionnaires. Samples were examined by microscopy, and B. coli was identified by PCR targeting ITS1–5.8S–ITS2, followed by Sanger sequencing. The gut microbiota was characterized using 18S and 16S rRNA (V3/V4) molecular markers for metabarcoding. Among the 47 participants, seven (14.9%) tested positive for B. coli nucleotide sequences in their fecal material, with most of them (71.4%) being adult males directly involved in pig handling. Phylogenetic analysis revealed genetic variants A0, B0, and atypical strains shared between humans and pigs from the same farm. Eukaryotic parasites ( B. coli , Blastocystis spp., Entamoeba spp.) and prokaryotic groups (Firmicutes, Bacteroidota, and potentially pathogenic bacteria) were also shared across hosts, and two human–pig pairs (H31–129F and H70–565F) exhibited highly similar microbial profiles. This study provides the first molecular evidence of B. coli in pig farmers in Brazil, reinforcing the epidemiological role of pigs in zoonotic transmission. These findings highlight the need for improved sanitation, consistent use of personal protective equipment, and continuous molecular surveillance under a One Health perspective to minimize transmission of this parasite.